Convergence in Income Inequality across the EU-15 - ARI, ALİ (My University, 2022)
The purpose of this study is to examine whether there is convergence in income inequality across the European Union-15 (EU-15) member countries over the 1988-2017 period. The system-GMM estimations suggest a significant convergence process in income inequality between EU-15 countries, but at higher values of the Gini coefficient. This ‘unpleasant’ result may indicate the inefficiency of extensive EU social and developmental projects and programs aimed at reducing national and regional disparities. The estimates also show more rapid convergence between the EU-15 countries when the country-specific economic and political control variables are included. On the other hand, our results indicate that an increase in FDI inflows leads to higher income inequality within individual countries while in countries where political rights and civil liberties are well established, income inequality tends to be lower.

Bu çalışmanın amacı, 1988-2017 döneminde Avrupa Birliği-15 (AB-15) üyesi ülkeler arasında gelir eşitsizliğinde yakınsama olup olmadığını incelemektir. Sistem-GMM tahminleri, AB-15 ülkeleri arasındaki gelir eşitsizliğinde, Gini katsayısının daha yüksek değerlerinde, önemli bir yakınsama sürecine işaret etmektedir Bu ‘hoş olmayan’ sonuç, AB’nin ulusal ve bölgesel eşitsizlikleri azaltmaya yönelik kapsamlı sosyal ve kalkınma proje ve programlarının verimsizliğine ișaret etmektedir. Tahminler, ülkeye özgü ekonomik ve siyasi kontrol değişkenleri de dahil edildiğinde AB-15 ülkeleri arasında daha hızlı yakınsama olduğunu da göstermektedir. Öte yandan, model sonuçları doğrudan yabancı sermaye girişlerindeki artışın ülkelerde daha yüksek gelir eşitsizliğine yol açtığını, siyasi haklar ve sivil özgürlüklerin iyi olduğu ülkelerde ise gelir eşitsizliğinin daha düşük olma eğiliminde olduğunu göstermektedir.
AB-15 ülkeleri arasında gelir eşitsizliği yakınsaması
Keywords: Income inequality; Inequality convergence; EU-15; System GMM; Gelir eşitsizliği; Gelir eşitsizliği yakınsaması; AB-15; Sistem GMM